Discursive Construction of Hamemayu Hayuning Bawana: Cultural Political Communication in Yogyakarta’s Infrastructure Development - Muhammad Rafi Fadilah (Program Studi Ilmu Pemerintahan Universitas Mulawarman, 2026)
Infrastructure development in Yogyakarta reflects an intersection between traditional authority and modern technocracy. While existing studies largely focus on land acquisition or economic impacts, limited attention has been given to how local philosophies are discursively recontextualized to frame large-scale spatial transformation. This study examines how Hamemayu Hayuning Bawana is articulated as a form of cultural political communication in the legitimation of National Strategic Projects, particularly the Yogyakarta International Airport and its supporting toll roads. Adopting a qualitative-interpretive approach, the research draws on a corpus of 10 documents comprising one gubernatorial speech transcript, three policy documents, and six media texts spanning 2021-2025, analyzed using Norman Fairclough's three-dimensional Critical Discourse Analysis. The study conceptualizes Hamemayu Hayuning Bawana as a discursive resource through which cultural meanings are mobilized in processes of political legitimation. The findings indicate a tendency toward semantic recontextualization, in which the cosmological meaning of Bawana is articulated in relation to technocratic-developmentalist terms such as global markets and investment gateways. Textually, this appears in collocations with growth-oriented vocabulary, euphemisms such as land acquisition for public interest, and passive constructions that background institutional agency. Discursively, the philosophy is circulated by actors holding both bureaucratic and customary authority, contributing to a hybrid discourse that combines administrative legality with Javanese ethical references. Socio-culturally, these formations may reframe potential agrarian tensions in moral-ethical terms, shaping how such issues are publicly articulated. This study suggests that Hamemayu Hayuning Bawana functions as a discursive element within broader processes of development legitimation and highlights the need to examine how local philosophies are mobilized in governance contexts.